Pressured By Perfection: A Tripartite Influence Model Approach to analyze Body Dissatisfaction, Self-Esteem, and Disordered Eating among Emerging Adult Females - Shahzadi, Hina; Bano, Shehar; Yousuf, Jawad (Journal of Development and Social Sciences, 2025)
This study set out to explore how young women are affected by the pressure to achieve a “perfect” body—particularly the thin, ideal image often seen in media and popular culture. It specifically looked at how this pressure relates to issues like low self-esteem, body dissatisfaction, and disordered eating behaviors among emerging adult females. In today’s image-driven world, young women are constantly surrounded by unrealistic beauty standards, often promoted by social media, celebrities, and societal norms. These external influences can deeply impact how they see themselves, leading to harmful comparisons and emotional distress. Using the Tripartite Influence Model, this study examines how these cultural and social forces contribute to the internalization of thin ideals and the resulting effects on mental and physical well-being. A quantitative approach was used, drawing data from 300 female university students aged 18 to 25, living in urban areas. Participants were selected through purposive sampling. Standardized questionnaires measured how much they internalized the thin ideal, their levels of self-esteem, and signs of disordered eating. The data were analyzed using statistical tools such as descriptive analysis, Pearson correlation, and multiple regression to identify meaningful patterns and relationships. The findings showed a clear connection between internalizing the thin ideal and experiencing lower self-esteem and unhealthy eating behaviors. Media and peer influence stood out as major factors contributing to body dissatisfaction. Many participants reported feeling pressured to meet unrealistic beauty expectations, which in turn led to harmful dieting habits and emotional distress. These results confirm the key ideas of the Tripartite Influence Model in the context of young women’s daily experiences. There is a strong need for programs that promote body positivity and help young women critically evaluate media messages. Schools, universities, and mental health professionals should work together to create supportive spaces where young women can talk about body image, build self-worth, and learn healthy habits without the burden of perfection.